Implementation of Project Based Learning Model Based on Pop-Up Book Media to Improve Student's Creativity In History Lesson - Viona Veronika; Syaiful Amin; Indri Siswanti (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to analyze the implementation of the Project-Based Learning (PjBL) model using Pop-Up Book media in enhancing students' creativity in history learning at SMA Negeri 1 Gebog Kudus. The research is motivated by the need to create learning experiences that encourage active student engagement and the development of 21st-century skills, particularly creativity. A descriptive qualitative method with a case study approach was employed, involving a history teacher and students from class XI F-8 as the research subjects. Data were collected through interviews, observations, and document analysis, and were analyzed using data triangulation techniques. The findings indicate that the implementation of PjBL with Pop-Up Book media effectively enhances the four indicators of student creativity: fluency in thinking, flexibility, originality, and idea elaboration. This suggests that the use of Pop-Up Book-based PjBL is a relevant and adaptable creative learning alternative across various educational levels and subjects.